2017
DOI: 10.3390/ijgi6010005
|View full text |Cite
|
Sign up to set email alerts
|

Combined Forecasting Method of Landslide Deformation Based on MEEMD, Approximate Entropy, and WLS-SVM

Abstract: Abstract:Given the chaotic characteristics of the time series of landslides, a new method based on modified ensemble empirical mode decomposition (MEEMD), approximate entropy and the weighted least square support vector machine (WLS-SVM) was proposed. The method mainly started from the chaotic sequence of time-frequency analysis and improved the model performance as follows: first a deformation time series was decomposed into a series of subsequences with significantly different complexity using MEEMD. Then th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Therefore, this proposed method has good performance in the fault diagnosis of rolling bearings. In order to further verify the superiority of EEMD over EMD and modified ensemble empirical mode decomposition (MEEMD) [42], the four groups of signals were decomposed by EMD and MEEMD respectively, and then GG clustering analysis was carried out. The results are shown in Table 4 and Figure 7.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Therefore, this proposed method has good performance in the fault diagnosis of rolling bearings. In order to further verify the superiority of EEMD over EMD and modified ensemble empirical mode decomposition (MEEMD) [42], the four groups of signals were decomposed by EMD and MEEMD respectively, and then GG clustering analysis was carried out. The results are shown in Table 4 and Figure 7.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…With the application of remote sensing techniques, surface deformation monitoring using high-resolution satellite data has been widely used and it can well realize the monitoring over a very large area. Many related studies have been carried out on surface deformation such as deformation in volcanoes [1], glacier movement [6][7][8][9][10], landslides [4,[11][12][13], permafrost [14], land subsidence [15,16], deformation in mining areas [5,[17][18][19][20] or other geohazards detections [2,[21][22][23][24]. A variety of approaches using interferometric synthetic aperture radar (InSAR) or space-borne differential InSAR have been used for the monitoring of mining-induced displacements in many mining areas [5].…”
Section: Introductionmentioning
confidence: 99%
“…Its main advantage is that it allows the use of a binary dependent variable-the occurrence of landslides in susceptibility mapping (Yilmaz, 2009;Ozdemir and Altural, 2013;Kavzoglu et al, 2014;Chan et al, 2018;Tian et al, 2019). In addition, methodological models, such as the frequency ratio model, multivariate adaptive regression splines, the generalized summation model, the deterministic factor method, the weight of evidence, and the entropy method have also been widely used in the spatial modeling of landslide hazards (Pardeshi et al, 2013;Xu et al, 2013;Jaafari et al, 2014;Regmi et al, 2014;Conoscenti et al, 2015;Youssef et al, 2015;Ilia and Tsangaratos, 2016;Xie et al, 2017;Ma and Xu, 2019). However, researchers have found that traditional mathematical methods were not sufficient to address the problems caused by the complexity of topography, geology, and other elements associated with the occurrence of landslide hazards: more flexible nonlinear methods were generally needed.…”
Section: Open Access Edited By 1 Introductionmentioning
confidence: 99%